TEXTURE OF THE GENRE “VÈ” - Triều Nguyên (Tạp chí Khoa học Đại học Đà Lạt)
“Vè” is widely acknowledged as a genre of Vietnamese folklore, introduced in many levels of the education system, but it is quite rare to research and learn about it. This paper presents the structure of “Vè” in two dimensions: The structure dependent on plot, consisting of three parts (introduction, description - i.e., telling the story, and ending); and The structure dependent on the characters’ personalities, dividing the people in a folktale into two types. At the same time, the author of this paper also compares the structure of “Vè” to that of some other types of narrative folklore (such as poetry, “Trạng” stories, fables, etc.). Today, there is limited research about “Vè”, so the problem that this paper addresses will be quite useful, and it is important to learn more about this genre.